PENYULUHAN MENGENAI PERAN MEDIA SOSIAL SEBAGAI BEKAL BERWIRAUSAHA DI SMK BERBUDI YOGYAKARTA - Artha, Bhenu; Asri, Cahya Purnama; Hadi, Antonius Satria (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2022)
This community service activity provides counseling to class XII students at SMK Berbudi Yogyakarta which aims to provide additional understanding and knowledge to class XII students about the relationship between social media and entrepreneurship so that later class XII students can open their own businesses after finishing school. This community service activity aims to increase understanding and additional knowledge for class XII students at SMK Berbudi Yogyakarta about the relationship between social media and entrepreneurship which is carried out using lecture, demonstration, and question and answer methods. The benefits that can be obtained by participants from this community service activity include increasing the knowledge, understanding, and experience of class XII students at SMK Berbudi Yogyakarta about the relationship between social media and entrepreneurship.